4th Independent Science Panel Meeting, Hanoi, Vietnam, 6–7 May 2013 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In May 2013 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its fourth Independent Science Panel meeting in Vietnam.